Cardiovascular response and backward, upward, right push maneuver during laryngoscopy: comparison between CMAC® video laryngoscopy and conventional Macintosh (Medical Journal of Indonesia, 2017)
Background: Increased blood pressure and heart rate are the most frequent response to laryngoscopy which sometimes causes serious complications. Laryngoscopy technique and tools modification lessen the nociceptive stimulation, thus preventing hemodynamic response. BURP maneuver is used to lower Cormack-Lehane level, but it can cause additional pain stimulation during laryngoscopy. The aim of this study was to compare the cardiovascular response and the need of BURP maneuver during laryngoscopy between CMAC® and conventional Macintosh. Methods: A randomized, single blinded, control trial was performed to 139 subjects who underwent general anesthesia with endotracheal tube. Subjects were randomised into a control group (conventional Macintosh) and an intervention group (CMAC®). The cardiovascular parameters (systolic, dyastolic, mean arterial pressure, and heart rate) were measured prior to induction (T1). Midazolam 0.05 mg/kg and Fentanyl 2 micrograms/kg were given 2 minutes before the induction. Moreover, they were given propofol 1 mg/kg followed by propofol infusion of 10 mg/kg/hour and Atracurium 0.8-1 mg/kg. After TOF-0 cardiovascular parameters (T2) were remeasured, it was proceeded to laryngoscopy. When Cormack-Lehane 1â2 was reached (with or without BURP maneuver), cardiovascular parameters were measured again (T3). Results: Unpaired T-test showed that cardiovascular response during laryngoscopy were significantly lower in the intervention group compared to the control group (p<0.05). The need of BURP maneuver was significantly lower in the CMAC® group compared to the Convensional Macintosh group (13.9% vs 40.3%; p<0.05). Conclusion: Cardiovascular response and BURP maneuver during laryngoscopy with CMAC® were significantly lower compared to conventional Macintosh.